2010
DOI: 10.4315/0362-028x-73.7.1238
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of on Inoculated Almonds Exposed to Hot Oil

Abstract: The heat resistance of Salmonella inoculated onto almonds was determined after immersion in hot oil. Whole almonds were inoculated with Salmonella Enteritidis PT 30 or Salmonella Senftenberg 775W and heated in oil. After heating, almonds were drained, transferred to cold tryptic soy broth, and mixed with a stomacher, and samples were plated onto tryptic soy and bismuth sulfite agars. Salmonella survivor inactivation curves were upwardly concave. Rapid reductions of 2.9, 3.0, or 3.6 log CFU/g for Salmonella Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 28 publications
4
43
1
Order By: Relevance
“…4% w/w moisture), which gives rise to concerns about the efficacy of roasting at mild processing conditions that maybe insufficient to eliminate salmonellae in nut processing. S. Enteritidis PT30 exhibited reasonably linear inactivation at the temperatures tested, which is in contrast to the results of Du et al (2010) where thermal inactivation results for S. Enteritidis PT30-inoculated almonds, immersed in hot oil, gave non-linear results. In addition, a study in peanut butter (Shachar & Yaron, 2006), also reported non-linear curves for the thermal inactivation of salmonellae (including S. Enteritidis).…”
Section: Inactivation Of the Heat Resistant Salmonella Strains In Crucontrasting
confidence: 96%
See 2 more Smart Citations
“…4% w/w moisture), which gives rise to concerns about the efficacy of roasting at mild processing conditions that maybe insufficient to eliminate salmonellae in nut processing. S. Enteritidis PT30 exhibited reasonably linear inactivation at the temperatures tested, which is in contrast to the results of Du et al (2010) where thermal inactivation results for S. Enteritidis PT30-inoculated almonds, immersed in hot oil, gave non-linear results. In addition, a study in peanut butter (Shachar & Yaron, 2006), also reported non-linear curves for the thermal inactivation of salmonellae (including S. Enteritidis).…”
Section: Inactivation Of the Heat Resistant Salmonella Strains In Crucontrasting
confidence: 96%
“…In addition, a study in peanut butter (Shachar & Yaron, 2006), also reported non-linear curves for the thermal inactivation of salmonellae (including S. Enteritidis). Both Du et al (2010) and Shachar and Yaron (2006), modelled the non-linear curves with the Weibull model. Different shapes of inactivation curves have been reported, including linear, sigmoidal ('shoulders' and 'tails'), concave and convex.…”
Section: Inactivation Of the Heat Resistant Salmonella Strains In Crumentioning
confidence: 99%
See 1 more Smart Citation
“…Since September 2007, in response to these outbreaks, almonds grown in California and sold in North America (U.S., Canada and Mexico) must be processed to achieve a minimum 4-log reduction of Salmonella using a validated process (Federal Register 2007). These processes may either induce desirable sensory characteristics (e.g., roasting or blanching) (Du, Abd, McCarthy, & Harris 2010) or may be designed to retain attributes of the raw almond (e.g., propylene oxide, high pressure, infrared heating, moist air impingement, steam or combination treatments) (ABC, 2007a;Bari et al 2009; Bari et al 2010;Brandl, Pan, Huynh, Zhu, & McHugh 2008;Chang, Han, Reyes-De-Corcuera, Powers, & Kang 2010;Jeong, Marks, & Orta-Ramirez 2009;Lee et al 2006;Willford, Mendonca, & Goodridge 2008;Yang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Almonds, in particular, were associated with two recorded outbreaks of salmonellosis [2,19], which led to the establishment of U.S. regulations that require treatment achieving a minimum 4-log reduction in Salmonella for California-grown almonds [10]. There are several treatments that can be used to meet the minimum reduction requirement including blanching [14], oil roasting [8], and propylene oxide fumigation [5,6]. However, blanching and oil roasting technologies may lead to undesirable loss of nutritional and physical quality and propylene oxide fumigation was found less attractive treatment for pathogen reduction due to its toxicity.…”
Section: Introductionmentioning
confidence: 99%